THE ANALYSIS OF SOUND TRANSMISSION LOSS ON LAMINATED GLASS - Fajar Budi Utomo; Bondan Dwi Setyo; Maharani Ratna Palupi; Chery Chaen Putri; Ninuk Ragil P.; Dodi Rusdjadi T. E.; Denny Hermawanto (Program Studi Fisika Universitas Negeri Jakarta, 2022)
Laminated glass is one type of glass that is commonly used for sound insulation (walls or doors). Tests related to the ability of insulating glass in Indonesia are still sporadic. One of the places to do this test is the SNSU BSN Lab. This Lab has a function to perform sound insulation level measurements commonly known as Sound Transmission Class (STC) and maintain to trace the ability of acoustic measurements. This paper describes the characteristics of Sound Transmission Loss (STL) of 12mm laminated tempered glass. The sample measurement method refers to ISO 10140-1 using two chambers (source and receiver room). Based on the study results, it was found that the laminated tempered glass sample was not good at reducing sound at low frequencies and tended to be good at high frequencies.